2020
DOI: 10.2298/tsci191223132f
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and optimization control of finned heat dissipation performance for automobile power lithium battery pack

Abstract: To cope with the problem of global warming and improve the performance of electric vehicles, the power source of electric vehicles is researched. First, the CFD simulation analysis method is utilized to analyze the heat dissipation effect under the changes of the air intake speed, the number of fins, and the thickness of the fins between lithium batteries. Then, the orthogonal experiment is utilized to select the optimal solution between the lithium batteries. The simulation results show that the heat dissipat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Qian X et al analyzed the influence of the battery spacing distribution and inlet air flow on temperature, and obtained the optimal parameter combination. Feng et al designed a finned heat exchanger with secondary heat exchange characteristics for the air-cooled battery pack, which expanded the heat exchange process and improved the heat exchange efficiency [19]. Xiaoming et al considered the transient thermal power of the longitudinal cell and studied the effects of three working conditions (continuous deceleration, continuous acceleration and pulse discharge) on the temperature rise and temperature difference of the air-cooled battery pack [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qian X et al analyzed the influence of the battery spacing distribution and inlet air flow on temperature, and obtained the optimal parameter combination. Feng et al designed a finned heat exchanger with secondary heat exchange characteristics for the air-cooled battery pack, which expanded the heat exchange process and improved the heat exchange efficiency [19]. Xiaoming et al considered the transient thermal power of the longitudinal cell and studied the effects of three working conditions (continuous deceleration, continuous acceleration and pulse discharge) on the temperature rise and temperature difference of the air-cooled battery pack [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the existing air-cooled battery module designs use a single air inlet and outlet, which may cause differences in cooling air flow between batteries, and increase the temperature difference of the battery pack. Therefore, some scholars improve uniformity of the temperature in lithium-ion battery pack of electric vehicles by changing the battery arrangement or the position of the airway [18] [19], but the volume of the battery pack is increased and the volumetric energy density is reduced, which affects the energy economy of electric vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Considering these factors, air cooling method is studied by Xun et al [12], during the research, many cooling systems were adopted, the results shown that for same type of channel, enlarging the channel dimension could enhances the cooling ability but it would cause more unbalanced, and vice versa. Subsequently, air intake velocity, fin count, and the thickness of the fin are utilized as research factors to investigate the heat transfer ability, the optimal combination of the cooling structure for Liion batteries is obtained by Feng et al [13], the research results show that the heat dissipation ability could improve by adopted the optimal combination. Similarly, for phase change material, its special physical properties have attracted many scholars, which can absorb or release heat during phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, due to their advantages of high efficiency, simple structure, high driving comfort, and low emissions, electric vehicles have become more and more accepted by people, and have reached a more practical stage. However, the problem of low cruising range in low-temperature conditions continues to be one of the main obstacles restricting their development [1][2][3]. Therefore, under the premise that the heating demand of electric vehicles is guaranteed in a low-temperature environment, it is important to reduce the shortening of the cruising range as much as possible for the development and popularization of electric vehicles.…”
Section: Introductionmentioning
confidence: 99%